Terapi Aktivasi Perilaku dapat mengurangi simtom anhedonia pasien skizofrenia ? - Tri Wiganti Andayani; Uun Zulfiana (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The goal of the intervention is to reduce the negative symptoms of people with schizophrenia. The assessments used were interviews, observations, and psychological tests which included graphic tests (BAUM, DAP, HTP), WAIS, and SSCT. The client’s problem is that he loses the pleasure of doing daily activities that used to be fun or made him happy. The intervention uses Behavioral Activation Therapy by providing a daily activity schedule. The results of the intervention show a decrease in symptoms of anhedonia, marked by an increase in daily client activities including bathing twice a day, being on time in taking medication, praying and helping with homework